Learning Outcomes Completing Pantun Verses Using the Process Skills Approach through Manual Teaching Materials - Rani, Nur Udhwa Ashikin Mohd; Hashim, Zuraina (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe: 1) the learning outcomes of completing pantun verses using the process skills approach in manual teaching materials; 2) the similarity of learning outcomes of completing pantun verses using the process skills approach in manual teaching materials per sample group. This descriptive-quantitative study was conducted in 2024 at Sekolah Kebangsaan Ampang, Ampang, Selangor, Malaysia. The population of this study consisted of grade 6 students who participated in learning to complete pantun verses using the process skills approach in manual teaching materials, totaling 90 students divided into three parallel classes. The sample consisted of 75 students, with 25 students in each of the five sample groups. Data on the learning outcomes of completing pantun verses using the process skills approach in manual teaching materials were collected through a written test consisting of four multiple-choice options. Data on learning outcomes of completing pantun verses using the process skills approach in manual teaching materials were analyzed using parametric inferential statistical procedures, namely the one-sample t-test and the one-way ANOVA test. The results of the study: 1) the learning outcomes of completing pantun verses using the process skills approach in manual teaching materials were categorized as very high; 2) there is no difference in learning outcomes in completing pantun verses using the process skills approach in manual teaching materials per sample group.